A QUARTER OF THE CENTURY WITHOUT CHEKHOV: RE-EVALUATION OF VALUES (Proceedings of Southern Federal University. Philology, 2024)
DOI 10.18522/1995-0640-2024-1-37-46The article examines the reaction of the literary and theatre criticism in the USSR and Russian Diaspora on 25th Chekhov's commemoration. In the country, where socialism was being constructed, classical tradition was under attack, as well as Chekhov, who exerted his influence on the aesthetic system of dramaturgy in particular and theatre in general. In those conditions the play “The Weirdo” (1929) by Alexander Afinogenov, nurtured by the Revolution and seduced by the highest power, and his appearances and speeches at various disputes and in press, supporting “psychological realism” and best theatrical tradition of the Moscow Art Theatre, were perceived ambiguously.Key words: Chekhov, chekhovism, twenty-five years, criticism, new drama, classical traditions, MAT, Afinogenov, “The Weirdo”, revolutionary theatre